2022
DOI: 10.1002/cjce.24671
|View full text |Cite
|
Sign up to set email alerts
|

Updates on biogas enrichment and purification methods: A review

Abstract: The market for biogas production has been increasing every year all over the world. The use of biogas as an energy vector is accomplished through the most diverse applications, such as direct burning (thermal energy), internal combustion engines, and fuel cells. Besides direct applications, biogas can be used as a raw material for producing high added-value products, such as molecular hydrogen and renewable hydrocarbons, through a new enterprise concept, the biorefineries. Purity and quality control are determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 211 publications
0
8
0
Order By: Relevance
“…Considering the state of research into the biogas composition, it can be clearly indicated that the CO 2 concentration in biogas depends on several factors, such as (I) temperature, (II) pressure and (III) liquid content in the digester [41]. It is non-toxic gas; however, it decreases the calorific value of biogas, reduces its density, laminar flame speed and combustion efficiency [34,57,88]. This implies that its high content reduces the economic feasibility of direct biogas application [40] and limits its use mainly to heat and electricity generation.…”
Section: Characteristics Of the Main Biogas Impuritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the state of research into the biogas composition, it can be clearly indicated that the CO 2 concentration in biogas depends on several factors, such as (I) temperature, (II) pressure and (III) liquid content in the digester [41]. It is non-toxic gas; however, it decreases the calorific value of biogas, reduces its density, laminar flame speed and combustion efficiency [34,57,88]. This implies that its high content reduces the economic feasibility of direct biogas application [40] and limits its use mainly to heat and electricity generation.…”
Section: Characteristics Of the Main Biogas Impuritiesmentioning
confidence: 99%
“…In turn, the second step, called 'biogas upgrading', aims to separate CO 2 , typically down to 2% vol. Consequently, it allows to obtain biomethane with properties and a composition similar to those of natural gas [34] and meet the quality standards of natural gas grids [35]. It has been widely reported that effectively upgraded biogas, referred to as biomethane, should contain more than 95-97% CH 4 [14,[36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALP is currently considered a waste and occasionally it is transferred to other establishments, which generates an additional transportation cost, where the residual oil is extracted with solvents, or is conditioned for its correct final disposal, since it has a high polyphenol content (Roig et al, 2006; Solomakou & Goula, 2021). This, added to the high amount of waste generated after each olive oil campaign, has aroused interest in ALP valorization (Oliveira et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Biogases, mixtures of mostly methane and carbon dioxide, are an upcoming power resource advantageous in terms of greenness, sustainability, and climate protection. There are three kinds of biogases (Rasi et al 2011 ), those from anaerobic digestion of wastewater treatment sludge (Bougrier et al 2006 ; Appels et al 2008 ; De Arespacochaga et al 2020 ), those released from landfills (Bolan et al 2013 ; Kuhn et al 2017 ; Li et al 2019 ; De Arespacochaga et al 2020 ; Braganca et al 2020 ; Wang et al 2020 ), and those produced from agricultural wastes (Rasi et al 2013 ; Akhavan et al 2014 ; Foppiano et al 2020 ; Oliveira et al 2022 ). Digester gas contains siloxanes that were adsorbed to sludge out of sewage, coming from use of personal care products containing, e.g., D 4 and D 5 .…”
Section: Introductionmentioning
confidence: 99%